Enforcement of the Rule of Law in the Case of Ojol Run Over by BRIMOB: Criticism of Equality Before the Law - Muttafiyah, Siti Rifqiyatul; Silfa, Afrisa; Qoiriyah, Sariah Nailla; Rahmania, Annisa Marshanda; Maslukha, Synthia Dewi (Jurnal Ilmu Pendidikan dan Humaniora, 2026)
This study analyzes the application of the rule of law principle in cases of violence by officials against online motorcycle taxi drivers, focusing on the incident in which Affan Kurniawan died after being run over by a Brimob tactical vehicle. This case attracted public attention because it was considered to reflect unequal treatment under the law between officials and civilians. Using a qualitative approach and case study method supported by literature review, this study examines the chronology of events, institutional responses, and their relevance to the principles of the rule of law, equality before the law, and human rights protection as stipulated in the 1945 Constitution, the Criminal Code, the TNI Law, and the Human Rights Law. The findings of this study reveal a structural pattern of impunity for officials, weak internal accountability, overlapping military-civilian jurisdictions, minimal transparency, and power bias in the legal process. These conditions have resulted in civilians, especially ojol workers in the gig economy who are in a vulnerable position, not receiving equal legal protection. This study confirms that the handling of cases of violence by officials is still far from the ideal rule of law, and that more independent, transparent, and integrated accountability mechanisms are needed to ensure justice for victims and increase the legitimacy of security institutions